Monobehenin and Tribehenin as Modifiers in the Crystallization of Palm Oil and Palm Stearin. Issue 5 (25th February 2022) - Zhang, Lu; Chen, Zenghui; Zhang, Qing; Li, Hong; Li, Xuehong; Zhang, Hong
Abstract: In consideration of the higher melting points and beneficial physiological functions of behenic acid, the effects of high purity monobehenin (MB) and tribehenin (BBB) as crystallization modifiers are studied. With the addition of MB and BBB at various concentrations, differential scanning calorimetry, polarized light microscopy, and X‐ray diffraction are used to understand the change in the crystallization behavior of palm oil (PO) and palm stearin (PS). The addition of MB or BBB promotes nucleation and leads to an earlier onset of crystallization during cooling. Under isothermal conditions, BBB increases the number of crystals and reduces the crystal size of PO more efficiently than MB. The addition of BBB accelerates the formation of β polymorph in both PO and PS, while the addition of MB retards the β' → β transformation of PS. The underlying mechanisms are proposed. The importance of structural affinity, polymorphic matching, and the degree of under‐cooling are elucidated. Practical applications : Behenic acid‐containing glycerides as seed crystals have potential applicability in the development of healthier fats with tailored functionalities. This research is helpful to elucidate the effects of polymorphic matching, structural affinity, and the degree of under‐cooling on engineering the crystallization of functional fats. Abstract : The mechanisms of monobehenin and tribehenin as seed crystals in isothermal and nonisothermal crystallization of palm oil and palm stearin are studied. The better the structural affinity between seed crystals and the fats, the more conducive to the epitaxial growth of crystals; the lower the degree of under‐cooling, the more obvious the effect of seed crystals on heterogeneous nucleation.